2021
DOI: 10.1002/hbm.25373
|View full text |Cite
|
Sign up to set email alerts
|

Stability test of canonical correlation analysis for studying brain‐behavior relationships: The effects of subject‐to‐variable ratios and correlation strengths

Abstract: Canonical correlation analysis (CCA), a multivariate approach to identifying correlations between two sets of variables, is becoming increasingly popular in neuroimaging studies on brain-behavior relationships. However, the CCA stability in neuroimaging applications has not been systematically investigated. Although it is known that the number of subjects should be greater than the number of variables due to the curse of dimensionality, it is unclear at what subject-to-variable ratios (SVR) and at what correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…Working memory was negatively related to the other two domains. Notably, this linear relationship was achieved with a sample to feature ratio of 58/(3+3) ≈ 9.7, in line with recent recommendations for multivariate model stability (Helmer et al, 2020;Yang et al, 2021).…”
Section: Cognitive Performance Is Related To the Ec Profile Of Sz Pat...supporting
confidence: 87%
See 4 more Smart Citations
“…Working memory was negatively related to the other two domains. Notably, this linear relationship was achieved with a sample to feature ratio of 58/(3+3) ≈ 9.7, in line with recent recommendations for multivariate model stability (Helmer et al, 2020;Yang et al, 2021).…”
Section: Cognitive Performance Is Related To the Ec Profile Of Sz Pat...supporting
confidence: 87%
“…Cross-validation confirmed that such a linear association has some level of out-of-sample generalizability. To achieve a stable and generalizable CCA model, we had observed the sample to feature ratio of above nine (Helmer et al, 2020; Yang et al, 2021) using ensemble feature selection (Bin et al, 2016; Saeys et al, 2008). We shall now discuss the significance of the effective connections and cognitive domains that the feature selection procedure returned—and their contribution towards the connection-cognition model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations